2023
DOI: 10.3390/jox13040034
|View full text |Cite
|
Sign up to set email alerts
|

The Extracellular Vesicles Containing Inorganic Polyphosphate of Candida Yeast upon Growth on Hexadecane

Anton N. Zvonarev,
Ludmila V. Trilisenko,
Vasilina V. Farofonova
et al.

Abstract: The cell wall of Candida yeast grown on presence of hexadecane as a sole carbon source undergoes structural and functional changes including the formation of specific supramolecular complexes—canals. The canals contain specific polysaccharides and enzymes that provide primary oxidization of alkanes. In addition, inorganic polyphosphate (polyP) was identified in Candida maltosa canals. The aim of the work was a comparative study of the features of cell walls and extracellular structures in yeast C. maltosa, C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Another example is the likely involvement of polyphosphates in the formation of extracellular vesicles in the Candida yeast consuming hexadecane. The yeasts C. maltosa , C. albicans and C. tropicalis form extracellular vesicles when grown on hexadecane as the sole carbon source [ 102 ]. Electron-scanning microscopy showed that these vesicles were associated with the cell wall and may be biofilm components.…”
Section: Extracellular Vesicles As a Mode Of Compartmentalization Of ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Another example is the likely involvement of polyphosphates in the formation of extracellular vesicles in the Candida yeast consuming hexadecane. The yeasts C. maltosa , C. albicans and C. tropicalis form extracellular vesicles when grown on hexadecane as the sole carbon source [ 102 ]. Electron-scanning microscopy showed that these vesicles were associated with the cell wall and may be biofilm components.…”
Section: Extracellular Vesicles As a Mode Of Compartmentalization Of ...mentioning
confidence: 99%
“…The presence of polyP in these vesicles was demonstrated by fluorescence microscopy with DAPI, a fluorochrome which shows orange fluorescence with these polymers. The treatment of hexadecane-grown cells with yeast Ppx1 polyphosphatase led to the degradation of vesicles, observed by scanning and fluorescence microscopy, and the release of orthophosphate into the medium [ 102 ]. These results indicate the important role of polyP in the formation of extracellular vesicles in the Candida yeast consuming hexadecane.…”
Section: Extracellular Vesicles As a Mode Of Compartmentalization Of ...mentioning
confidence: 99%
See 1 more Smart Citation